Fiscal illusion as an incentive for local government public expenditure efficiency: The influence of community sensitization - Paul Onyango-Delewa (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
Although the effect of public expenditure efficiency on local government fiscal performance is widely-documented, what precisely explains expenditure efficiency remains largely unclear. Nevertheless, past research holds fiscal illusion as the most likely predictor and community sensitization very critical for fiscal illusion-expenditure efficiency formation. We employed fiscal illusion theory to investigate possible fiscal illusion-community sensitization-expenditure efficiency mediation in 16 districts, 6 municipalities, and 160 sub-counties of Uganda’s northern region. Over the years, Uganda; an East African country, is applauded for its fiscal federalism proficiency. But presently, its northern region is grappling a 20-year post-conflict trauma likely to compromise entity spending efficiency. Structural equation modeling results suggest that all the four fiscal illusion constructs: fiscal imbalances, political divide, tax payment bias, and fiscal sabotage, predict changes in expenditure efficiency. However, community sensitization does not mediate the fiscal illusion-expenditure efficiency linkages. Implications for these findings and possible direction for future research are discussed.